Qualitative Synthesis of Acupuncture and Moxibustion Experiences in Breast Cancer Survivors: Navigating Life as a Voyager Beyond the Waves of Survival - Sunjoong Kim; Jisu Ha; Sohyeon Ryu; Seungjin Noh; Yejin Hong; Inae Youn (Journal of Acupuncture Research)
Breast cancer remains the most prevalent malignancy that affects women worldwide. The present study aimed to provide foundational data to improve the therapeutic approaches through a qualitative meta-synthesis of the experiences of breast cancer survivors with acupuncture and moxibustion. Using Noblit and Hare’s meta-ethnography methodology, 11 qualitative studies exploring the experiences of breast cancer survivors were selected and meta-synthesized. The quality of the included studies was evaluated using the Consolidated Criteria for Reporting Qualitative Research and Standards for Reporting Qualitative Research criteria. The quality evaluations of individual studies revealed insufficient information provided by researchers, with a notable absence of gender-related information. The qualitative synthesis identified the following three primary themes: the distress associated with conventional breast cancer treatment protocols, a desire for comprehensive care and support, and a holistic treatment approach facilitated by acupuncture and moxibustion. This study elucidated the unmet medical needs of breast cancer survivors in terms of holistic treatment and preservation of human dignity, confirming that acupuncture and moxibustion partially address these needs. Our study findings may serve as foundational data for healthcare professionals providing acupuncture and moxibustion treatment to breast cancer patients in future clinical practice.